Exploration of the MUC5B promoter variant and ILD risk in patients with autoimmune myositis. (September 2017) - Johnson, Cheilonda; Rosen, Paul; Lloyd, Thomas; Horton, Maureen; Christopher-Stine, Lisa; Oddis, Chester V.; Mammen, Andrew L.; Danoff, Sonye K.
Abstract: Interstitial lung disease (ILD) is common in patients with autoimmune myositis but factors that determine susceptibility are unknown. Familial and sporadic idiopathic pulmonary fibrosis (IPF) are strongly associated with a single nucleotide polymorphism in the promoter region of MUC5B (rs35705950). We sought to determine the relationship between MUC5B polymorphism expression and myositis-ILD. The MUC5B minor allele frequency (MAF) was examined in 402 European American participants; 60 with idiopathic interstitial pneumonia (IIP), 208 with myositis-ILD, and 134 unaffected controls. The MUC5B minor allele frequency was 26%, 8%, and 7% in those with non-myositis ILD, myositis-ILD, and unaffected controls, respectively. The MUC5B variant was associated with IIP (OR 4.10; p  < 0.001). The MUC5B polymorphism was not significantly associated with myositis-ILD (OR 1.08; p = 0.80)]. We found MUC5B MAFs in our IIP cohort similar to published frequencies for subjects with familial and sporadic IPF. Overall, the MUC5B promoter variant does not appear to contribute to ILD risk in myositis patients. Highlights: IPF is strongly associated with a SNP in the promoter region of MUC5B (rs35705950). Determining shared genetic risk factors is key to understanding ILD mechanisms. We found that the MUC5B variant does not contribute to risk in myositis-ILD.